2017
DOI: 10.1161/jaha.116.005285
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Cardiovascular Trials With Primary Surrogate Endpoints: 1990–2011

Abstract: BackgroundSurrogate endpoint trials test strategies more efficiently but are accompanied by uncertainty about the relationship between changes in surrogate markers and clinical outcomes.Methods and ResultsWe identified cardiovascular trials with primary surrogate endpoints published in the New England Journal of Medicine, Lancet, and JAMA: Journal of the American Medical Association from 1990 to 2011 and determined the trends in publication of surrogate endpoint trials and the success of the trials in meeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…For instance, trials have compared new agents with placebos rather than the best existing therapies, underdosed comparator drugs, or relied on surrogate endpoints65 that may not predict outcomes. Some commercially funded researchers have also selectively published (and republished) positive results 866 or concealed negative findings,67 while firms have ended trials prematurely for purely commercial reasons 68…”
Section: Clinical Testingmentioning
confidence: 99%
“…For instance, trials have compared new agents with placebos rather than the best existing therapies, underdosed comparator drugs, or relied on surrogate endpoints65 that may not predict outcomes. Some commercially funded researchers have also selectively published (and republished) positive results 866 or concealed negative findings,67 while firms have ended trials prematurely for purely commercial reasons 68…”
Section: Clinical Testingmentioning
confidence: 99%
“…A biomarker is believed to be a characteristic indicator of normal biological processes, pathogenic processes, or pharmacological responses to therapeutic interventions [10,11]. In contrast, clinical endpoints are considered as variables representing a study subject's health from his/her perspective [12][13][14][15][16][17][18][19][20][21][22]. A variety of biomarkers exist today as surrogates to access clinical outcomes in diseases, predict the health of individuals, or improve drug development.…”
Section: Micro (Mi) Rnas As Biomarkers and Their Roles In Disease Prmentioning
confidence: 99%
“…In this issue of JAHA , Bikdeli et al provide documentation from an examination of the literature that shows that building cardiovascular clinical therapeutics from trials based solely on unvalidated biomarkers would be folly . The authors extracted information from 3 prominent medical journals, focusing on clinical trials that used biomarkers as primary outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of JAHA, Bikdeli et al provide documentation from an examination of the literature that shows that building cardiovascular clinical therapeutics from trials based solely on unvalidated biomarkers would be folly. 2 The authors extracted information from 3 prominent medical journals, focusing on clinical trials that used biomarkers as primary outcome measures. As previous reports would suggest, they found that the majority of these studies either were not followed by trials measuring a clinical outcome as a primary endpoint, or, when such trials were done, they found that the positive biomarker findings were not associated with better clinical outcomes.…”
mentioning
confidence: 99%